2014
DOI: 10.1016/j.scitotenv.2013.11.091
|View full text |Cite
|
Sign up to set email alerts
|

Routine screening of harmful microorganisms in beach sands: Implications to public health

Abstract: Beaches worldwide provide recreational opportunities to hundreds of millions of people and serve as important components of coastal economies. Beach water is often monitored for microbiological quality to detect the presence of indicators of human sewage contamination so as to prevent public health outbreaks associated with water contact. However, growing evidence suggests that beach sand can harbor microbes harmful to human health, often in concentrations greater than the beach water. Currently, there are no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 111 publications
(137 reference statements)
1
55
0
7
Order By: Relevance
“…3 Escherichia coli counts in dry and wet sands at Gonzaguinha and Ilha Porchat beaches during the study period. Error bars indicate standard error of the mean to public health, once that beachgoers spend more time in sand than in the seawater, and a widely variety of pathogens should be included for screening on different sand zones (Halliday and Gast 2011;Sabino et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…3 Escherichia coli counts in dry and wet sands at Gonzaguinha and Ilha Porchat beaches during the study period. Error bars indicate standard error of the mean to public health, once that beachgoers spend more time in sand than in the seawater, and a widely variety of pathogens should be included for screening on different sand zones (Halliday and Gast 2011;Sabino et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Pathogens may persist and/or re-grow in beach sand driven by periodic wetting through wave heights and tides and the concentration of fecal indicators in sand may be even greater than that observed in RW (Halliday and Gast 2011). Soils are also a relevant source of pathogens and may have concentrations of microorganisms up to 100-fold higher than in nearby waters (Sabino et al 2014). The pathogens can be deposited on the land surface and subsequently conveyed to the stream during and after rainfall events achieving the RW (Ogden et al 2009).…”
Section: Microbial Pathogens In Recreational Watersmentioning
confidence: 99%
“…These studies also aim to draw conclusions leading to the possibility of controlling the safety of beach sands. Of particular interest are the studies of Sabino et al [42,43] and Pereira et al [41] who investigated the beaches in Portugal and the Madeira archipelago. Sabino et al [43] found in the sand Trichophyton and Microsporum species, but no Epidermophyton.…”
Section: Beach Sand and Dermatophytosesmentioning
confidence: 99%